Sistemas de manejo e uso do solo sobre as frações e estoques de carbono e nitrogênio em Latossolo sob cerrado - Silva, Geanderson Nascimento da (2016)
The misuse of the soil promotes the reduction of organic carbon, which provides favorable conditions for loss of quality. The objective of this study was to evaluate the content and stock of carbon, nitrogen and its fractions in soils under different land uses and managements in the Cerrado. The treatments were: native Cerrado (reference), no-tillage18 years, area under coffee for 11 years and crop-livestock integration for 2 years. The total organic carbon were influenced by land use systems and soil management, where the native Cerrado had stock of 74.3 Mg ha-1, followed by no-tillage with 58.8 Mg ha-1, coffee with 56.4 Mg ha-1 and crop-livestock integration whit 50.8 Mg ha-1. The stocks of total nitrogen followed similar behavior to the total organic carbon stocks in the native Cerrado presented 4.84 Mg ha-1, followed by no-tillage with 3.71 Mg ha-1, coffee with 2.87 Mg ha-1 and crop-livestock integration with 2.47 Mg ha-1. The stocks of particulate organic carbon were at 8.7, 10.1, 12.8 and 16.5 Mg ha-1 to no-tillage, coffee, crop-livestock integration and native Cerrado, respectively. Crop-livestock integration systems such as conservation tillage on for 2 years sand no-tillage for 18 years were not enough to lift the stocks of total organic carbon, total nitrogen and its fractions to the original levels (Cerrado).